Learning at SMA Muhammadiyah 4 Porong during The Pandemic Covid 19 - Avinda Virnadya Kuswantoro; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The COVID-19 pandemic is a major challenge for the education system. This viewpoint offers guidance for teachers, heads of Institutions in dealing with crises. What preparations do institutions have to undertake in a short period of time and how do they meet the needs of students by level and field of study? Reassuring students and parents is an important element of the institutional response. In increasing capacity to teach remotely, schools and colleges should take advantage of asynchronous learning. So this study aims to analyze learning in the midst of the covid-19 pandemic. This study used a qualitative method that relied on data obtained from interviews conducted in a natural setting. This research was conducted at the Muhammadiyah vocational school level which examined the history of school formation and school activities. Because the research took place during the pandemic period, the researchers also examined methods, media, and constraints for learning. The data were then collected, analyzed and concluded as statements.